1999
DOI: 10.1080/0300443991570105
|View full text |Cite
|
Sign up to set email alerts
|

Center Care and Education in Bahrain: Does It Benefit Children's Development?

Abstract: The purpose of this study was to examine the role of preschool education in Bahrain by studying the effects of three different preschool settings (care-oriented, educationallyoriented, and home) on children's cognitive and socio-emotional performance. A profile of six culturally adapted and translated (Arabic) parametrical instruments were used to measure children's progress (W = 140; M age = 48.7 months) over one academic year. Multiple regression analysis which considered several family and school background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In some instances associations were lower than most in the US, for example in Bahrain (Hadeed & Sylva, 1999). That said, it is not altogether clear how best to interpret these findings.…”
Section: Stimulation/teachingmentioning
confidence: 76%
See 1 more Smart Citation
“…In some instances associations were lower than most in the US, for example in Bahrain (Hadeed & Sylva, 1999). That said, it is not altogether clear how best to interpret these findings.…”
Section: Stimulation/teachingmentioning
confidence: 76%
“…When the Early Childhood HOME was used in Bahrain, a very broad range of scores emerged (Hadeed & Sylva, 1999). The mean score was about 1 / 3 SD lower in Bahrain than in the US.…”
Section: Stimulation/teachingmentioning
confidence: 98%
“…Although HOME shows generally strong relations with cognitive and language competence, it may not contain sufficient indicators of the experiences needed to promote particular competencies (e.g., science, art, psychomotor learning). It is also important to recognize that relations may differ depending on children's health status, parent mental health, time spent in nonparental care, and family demographics (Adi‐Japha & Klein, ; Baydar et al, ; Bradley et al, ; Bradley et al, ; Bradley et al, ; Church & Katigbak, ; Coscia et al, ; Davidson, Myers, Shamlaye, Cox, & Wilding, ; Hadeed & Sylva, ; Holditch‐Davis, Tesh, Goldman, Miles, & D'Auria, ; Johnson, Breckenbridge, & McGowan, ; Richter & Grieve, ; Wulbert et al, ). In poor communities, for instance, the dearth of material goods and opportunities for enrichment, poor nutrition, family instability, and accumulated health problems sometimes resulted in lower correlations, thereby prompting some scholars to make changes in HOME items (Holding, Abubakar, Obiero, Barr, & van Vijver, ; Kohli, Mohanty, & Kaur, ; Lozoff et al, ).…”
Section: Relations With Parent Characteristics Family Context and Cmentioning
confidence: 99%
“…On the basis of knowledge of how children learn, German researchers added indicators to the language stimulation subscale that reflect child‐friendly approaches to parents' use of language connected to learning (Blomeyer et al, ). Cultural models of parenting in Arab countries typically do not place as much emphasis on stimulation of school achievement as is true for Western democracies and Asian countries like Taiwan, South Korea, and Japan (Bradley, ; Hadeed & Sylva, ). In parts of Africa and Asia, greater attention is given to teaching practical skills and self‐care, especially where there is poor community infrastructure.…”
Section: Relations With Parent Characteristics Family Context and Cmentioning
confidence: 99%
“…The subscales are: stimulation through toy; games and reading materials; stimulation for communicative competence; physical environment -safe, clean and conducive to development; pride, affection and warmth; stimulation of academic behaviour; modelling and encouragement of social maturity; variety of stimulation and physical punishment. The HOME scale has been used in previous research in Bahrain (Hadeed, 2005;Hadeed & Sylva, 1999). The results (total scores) indicated that the programme intervention households did not significantly differ from the control households, t(167) = −.38, p < .69, during primary schooling stages.…”
Section: Home Environment Resultsmentioning
confidence: 95%